2021
DOI: 10.1002/bse.2738
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the mission statements of benefit corporations: Empirical evidence from Italy

Abstract: In 2015, Italy introduced a new legal form-"benefit corporation" (società benefit)that provides legal status to companies that have one or more common benefit objectives in addition to the profit-seeking goal. Italian benefit corporations are obligated by law to operate in a responsible, sustainable, and transparent way and to include the interests of different stakeholders in their corporate strategy. This study examines the Italian case by applying textual statistical analysis on benefit corporations' public… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 81 publications
(115 reference statements)
0
9
0
Order By: Relevance
“…Lastly, the common traits of firms that are recognized as BCs. A previous analysis conducted in Italy (Mion et al, 2021) has focused its attention on the information that could be found on the website of a sample of BCs, while we conducted our analysis directly inside the AoA, where the specific common benefit pursued by companies could be detected.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, the common traits of firms that are recognized as BCs. A previous analysis conducted in Italy (Mion et al, 2021) has focused its attention on the information that could be found on the website of a sample of BCs, while we conducted our analysis directly inside the AoA, where the specific common benefit pursued by companies could be detected.…”
Section: Introductionmentioning
confidence: 99%
“…SBM research might examine how such distributive design traits function (Dekhili & Achabou, 2013; Mjahed Hammami et al, 2018; Norris et al, 2021). The literature on social businesses (Gold et al, 2020; Schrader et al, 2012), social entrepreneurship (Enthoven & Thelken, 2022) and benefit corporations (Liute & De Giacomo, 2022; Mion et al, 2021; Stubbs, 2017) could provide valuable insights for this avenue of research.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, signing a legally binding contract with a third‐party stakeholder that entitles them to sue the company for damages if the commitment is broken could be a powerful way to “tie one's hands” in the future period. Other ways to disable discretion could be to change the legal form of the company to one that is mandated to be concerned about its social and environmental impacts, for instance, via converting to a benefit corporation or implementing other forms of stakeholder governance, as Patagonia has done alongside over 4900 other companies around the world (B Lab, 2022; Mion et al, 2021; Rawhouser et al, 2015). Alternatively, companies could lobby for government regulation that ties their hands for them, for example, via due diligence legislation (Bager et al, 2021) or import bans on unsustainable or illegal products such as the Lacey Act Amendment (Eberhardt, 2013).…”
Section: Credibility In Future Commitmentsmentioning
confidence: 99%